(untitled) (Bangladesh Journal of Agricultural Research, 2014)
The study was conducted in two districts Comilla and Jessore to examine the marketing chain, marketing cost, and margin, problems and some probable solutions for cabbage and cauliflower marketing. A total of 92 respondents consisting of 20 vegetable growers and 72 vegetables traders were selected as sample for the present study. A multi-stage simple random sampling technique was used for selection of samples. Both primary and secondary data were used for the study. About 60% farmers used van to carry the vegetables to the market. Average cauliflower marketing cost of farmer was higher than cabbage which was Tk.36.59 per quintal due to its special transportation arrangement. On the basis of the intermediaries, seven marketing chain were identified as a dominant. The chain Farmer?Local Traders (Faria) ? Bepari? Aratdar (urban) ?Retailer (urban) ?Consumer was identified as most dominant. About 39.60% product runs through this chain. In cauliflower marketing local traders, Bepari, retailer (urban) and retailer (rural) incurred the highest marketing cost than cabbage which were averaged Tk.65.75, Tk.248.47, Tk.205.69, and Tk.78.21, respectively, due to its perishable nature. In the case of farmers, local traders (Faria) and Bepari transportation cost is the highest. Commission charge was highest in the case of retailer (urban) and spoilage and damage cost was the highest for retailer(rural).The marketing cost was the highest for Bepari which were estimated Tk.212.74 for cabbage, Tk.219.87 for cauliflower and the marketing margin was highest for retailer (urban) which were estimated Tk.108.52 for cabbage and Tk.130.09 for cauliflower. Inadequate storage facilities and dominance of intermediaries were the major marketing problems identified by the farmers. Unstable price, barrier to entry in the terminal market, delays on ferryghat and spoilage and damage were the major marketing problem faced by the different intermediaries. The study suggested improving the storage facilities and establishment of organization to solve marketing problem of the farmers. Easy access of vegetables carrying vehicle in the terminal market, arrangement of separate cargo ferry would reduce the spoilage and damage of vegetables in the traders level. DOI: http://dx.doi.org/10.3329/bjar.v39i1.20163 Bangladesh J. Agril. Res. 39(1): 127-141, March 2014